PENGEMBANGAN MODEL ASSESSMENT for LEARNING (AfL) MELALUI PENILAIAN TEMAN SEJAWAT PADA PEMBELAJARAN MATEMATIKA PADA POKOK BAHASAN TRIGONOMETRI DITINJAU DARI GAYA BELAJAR SISWA SMA NEGERI KARANGPANDAN TAHUN PELAJARAN 2012/2013 - Dismas Suparmo; Budiyono Budiyono; Sutanto Sutanto (Jurnal Pembelajaran Matematika, 2013)
ABSTRACT : The aims of this research were: (1)to determine whether the AfLwith peer assessment of trigonometry topics can be applied in Karangpandan Senior High School, (2) to know which is more effective of the application of the AfL with peer assessment in improving students’ achievement compare with direct instruction,(3) to know the influence of students’ learning styles toward mathematics learning achievement of students in the trigonometry subject, (4)to determine the effect of the application of the AfL with peer assessment in improving student achievement be compared with direct instruction in terms of students' learning styles on trigonometry subject. The research was dividedi nto two phases, the first phase is the determination of the model development stage and the AfL with peer assessment are included in research and development. In this stage, be done data collection, prototype planning model,Focus Group Discussion (FGD) were implemented and manufacture of prototype model then be tested. Tests carried out by 4 learning cycles.The second phase was to test the effectiveness of a model that includes quasi-experimental research by design research 2×3. The population of this research was eleven grade students of Karang pandan Senior High School of the first semester of the academic year 2012/2013. Samples were divided into two groups,experimental and control groups. The data analysis technique of this research that being used inthis study was unbalanced two-way analysis of variance.Based on the result of the analysis, we can conclude that:(1) the model of the AfL with peer assessment can be applied in Karangpandan Senior High School State. During the implementation of theAfL with peer assessment, the students being involved in learning and assessment learning, so more enjoyable and mathematics achievementof students is also increasing (2)students taught using AfL with peer assessment have mathematics achievement better than students taught using direct instruction, (3) students with kinesthetics learning style have higher mathematics achievement thanstudents with visual and auditory, while students with a visual learning style have a better achievement than students with auditory learning style, (4)at all the kinds of learning styles, students with applied learning AfL with peer assessment have better mathematics achievement than students with direct learning.Keywords: Assessment, Assesment for Learning (AfL), Peer Assessment, Learning Styles